(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: ectopic pregnancy EP is implantation of fertilized ova outside the uterine cavity and most commonly in the tube 98% with a prevalence of 1-2% from all spontaneous pregnancies all over the world. Objective: to evaluate the most common organisms associated with tubal ectopic pregnancy isolated from female genital tract byendocervical swab using multiplex real time PCR.Patients and Methods: a prospective cross sectional study conducted in the Department of Obstetrics and Gynaecology, Baghdad Teaching Hospital, 30 patients participate in this study, all of them diagnosed as tubal ectopic pregnancy some of them emergency cases and others are elective cases scheduled for laparoscopic surgery, endocervical swab was taken and sent for laboratory analysis by multiplex real time PCR technique using a panel of microorganisms including Niesseria gonnorhoea NG, Chlamydia trachomatis CT, Mycoplasma hominis MH, Ureaplasma Vrealyticum UU, T richomonas Vaginalis TV, Gardenerella vaginalis GV,Enterococci, and Staphylococcus aureus.Results: The most common microorganism associated with ectopic pregnancy found by multiplex real time PCR in the iraqi patients in this study was UU 10 (33.4%), then UU+ enterococci and CT in 7 23.3%, and one case 3.3% with Staph Aureus and one case 3.3% with UU+ enterococci and Staph Aureus.Conclusion: Ureaplasma urealyticum bacteria a common organism found in the cervix of Iraqi women diagnosed with ectopic pregnancy as a uni-organism or mixed infection which calls for intensifying efforts to conduct careful screening for upper genital infections in the high risk group using endocervical swab which is easy, non-invasive, and applicable method being analysed by multiplex real time PCR for the organisms of interest which is highly sensitive procedure and the results obtained within short time which allows starting effective treatment and hence prevention of ectopic pregnancy, further researches required to determine the presence of UU and other microorganisms in the affected tubes.